2021
DOI: 10.5430/ijhe.v10n3p285
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education in the First Year of COVID-19: Thoughts and Perspectives for the Future

Abstract: In the last year a new virus (SARS‑CoV‑2) and the disease caused by it (COVID-19) has quickly spread around the world, leading the World Health Organization to declare a public health emergency and, then, a global pandemic status. The strategies adopted by many countries to reduce the impact of the pandemic were mainly based on social distancing rules and on stay-at-home measures or lockdowns. These strategies had severe disruptive consequences on many sectors, including all levels of education. While the “tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 6 publications
4
45
0
1
Order By: Relevance
“…Moving forward, it will be important to cultivate a normal that blends technology with the intimacy and efficacy of in-person instruction (Cesco et al, 2021). Universities will need to make thoughtful decisions and provide technology support and infrastructure for faculty (Moreira, 2016;Toquero, 2020).…”
Section: Discussionsupporting
confidence: 72%
“…Moving forward, it will be important to cultivate a normal that blends technology with the intimacy and efficacy of in-person instruction (Cesco et al, 2021). Universities will need to make thoughtful decisions and provide technology support and infrastructure for faculty (Moreira, 2016;Toquero, 2020).…”
Section: Discussionsupporting
confidence: 72%
“…A recent bibliographic analysis revealed that there are a number of theoretical papers that have been published in the last eighteen months on this hot topic (Cesco et al, 2021;Fitter et al, 2020;Howley, 2020;Rahiem, 2020). Yet, to date, there are just a few rigorous studies, that examined the utilization of synchronous video conferencing technologies, in addition to conventional, asynchronous content, like LMS, in the context of higher education (Aguilera-Hermida, 2020;Gonzalez et al, 2020).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The lack of technological resources along with a space to study has deeply impacted students, especially those from a lower socio-economic status (Cabero & Valencia, 2021;Adedoyin & Soykan, 2020). In education, research has confirmed time and again that major challenges faced by the education community are lack of resources and infrastructure (Zhang et al, 2020), lack of reliable internet connection (Xie et al, 2020;Cesco et al, 2021;Tabassum et al, 2021;Hebebci et al, 2020;Lapada et al, 2020;Yusuf & Ahmad, 2020), insufficient digital literacy among teachers and students (Almazova et al, 2020;Adedoyin & Soykan, 2020), lack of and the need of training in the use of technological tools (Santos et al, 2020;Yusuf & Ahmad, 2020) and lately, socio-emotional and stress factors affecting students and teachers (Hadar et al, 2020;Marsollier & Expósito , 2021;Lapada et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, research has also reported positive views on the implementation of large-scale technology mediated education during and after the pandemic. Among the major topics we can highlight teachers' experience higher levels of self-efficacy and feel a sense of accomplishment at managing difficult student behavior online (Sokal et al, 2020), the opportunity for institutions to innovate their educational offer (Cesco et al, 2021), the emphasis on research innovation to personalize online learning models and support efforts to reduce workload of instructors along with the redesign of the learning process (Adedoyin & Soykan, 2020). Also, the availability of open educational practices and resources that played an important role during the pandemic as mechanisms and helped maintain the educational process (Bozkurt & Sharma, 2020) and the opportunity provided by online learning to serve as an alternative in times of crisis (Dhawan, 2020).…”
Section: Introductionmentioning
confidence: 99%